Delay in presentation of childhood cataract cases for surgery and its determinants in a tertiary care hospital of Kolkata during the Covid-19 pandemic period: a cross-sectional study - Smiti R. Srivastava; Sagar Karmakar; Jayeeta Mazumder; Sinjita Dutta (Al Ameen Medical College, 2023)
Background: In India the already existing problem of late detection and late presentation of childhood cataract got further worsened during Covid lock down period due to disruption of regular services delivery, lack of transport and fear of getting Covid infection leading to a massive reduction in hospital attendance. This study was done to find out the delay in presentation of pediatric cataract cases along with its determinants during the covid-19 pandemic and lockdown. Methodology: A descriptive, observational study was conducted among 96 paediatric cataract patients attending ophthalmology OPD of IPGMER during April 2020 to March 2021. Patients were subjected to ophthalmological examination to find out the laterality and type of cataract. Principal care givers of the patients were interviewed to study the socio-demographic, Covid related and clinical variables. Result: Mean age of study population was 4.18±2.99 completed years. 90% of patients residing in rural areas reported with delay to the hospital which was statistically significant (p<0.05). Developmental and unilateral cataract cases had a significantly higher proportion of delayed presentation (p<0.05). Urban residence, bilateral cataract cases and patients with Covid-19 negative status of family members had significantly (p<0.05) lower odds of delayed presentation. Conclusion: Covid-19 lock down led to a reduction in hospital attendance due to non-availability of transport, Covid-19 positive family member, or loss of daily wages.